Pharmacotherapy for the management of the symptoms of Machado-Joseph Disease. (13th October 2022) - Oliveira, Jessica Blanc Leite; Martinez, Alberto R.M.; França Jr, Marcondes Cavalcante
ABSTRACT: Introduction: Machado-Joseph disease or spinocerebellar ataxia type 3 (SCA3/MJD) is the leading cause of autosomal dominant ataxia worldwide. This is a slowly progressive, but very disabling disorder. Ataxia is the main clinical feature, but additional motor and non-motor manifestations may be found. Many of these manifestations are amenable to pharmacological treatments, which may impact the quality of life of affected subjects. Areas covered: Authors review available literature on both disease-modifying and symptomatic pharmacological therapies for SCA3/MJD. Discussion is stratified into motor (ataxic and non-ataxic syndromes) and non-motor manifestations. Ongoing clinical trials and future perspectives are also discussed in the manuscript. Expert opinion: Symptomatic treatment is the mainstay of clinical care and should be tailored for each patient with SCA3/MJD. Management of ataxia is still a challenging task, but relief (at least partial) of dystonia, pain/cramps, fatigue, and sleep disorders is an achievable goal for many patients. Even though there are no disease-modifying treatments so far, recent advances in understanding the biology of disease and international collaborations of clinical researchers are now paving the way for a new era where more clinical trials will be available for this devastating disorder.